The Yin and Yang aspects of IL-27 in induction of cancer-specific T-cell responses and immunotherapy. (February 2015) - Li, Ming-Song; Liu, Zhenzhen; Liu, Jin-Qing; Zhu, Xiaotong; Liu, Zhihao; Bai, Xue-Feng
Accumulating evidences from animal studies have indicated that both endogenous and exogenous IL-27, an IL-12 family of cytokine, can increase antitumor T-cell activities and inhibit tumor growth. IL-27 can modulate Treg responses, and program effector T cells into a unique T-effector stem cell (TSEC ) phenotype, which enhances T-cell survival in the tumor microenvironment. However, animal studies also suggest that IL-27 induces molecular pathways such as IL-10, PD-L1 and CD39, which may downregulate tumor-specific T-cell responses. In this review paper, we will discuss the Yin and Yang aspects of IL-27 in the induction of tumor-specific T-cell responses, and the potential impacts of these functions of IL-27 in the design of cancer immunotherapy.